PREFERENCE OF JANDAÍRAS BEES FOR DIFFERENT TYPES OF WAX AND EXTERNAL FORAGING, IN THE HISTORY OF PARAIBA - A. Wanderley, Paulo; N. M. Alves, Davi; L. N Silva, Amanda; P. Sousa, Adinaele; I. Delfino, Francisco; I. M. Andrade, Maria; C. Andrade, Weliton; G. B. Batista, Renata; V. N. Carlos, Maria; L. A. da Silva, João (Journal of Interdisciplinary Debates, 2023)
The of stingless bees creation is an agricultural activity that has grown in recent years. In the Brazilian Northeast, Melipona subnitida is one of the most important species in the Semiarid region. Among the products, wax is a substance produced by worker bees and is the main material used in the construction of laying discs and food pots. The present work aims to study the preference and non-preference of Jandaíra bees to different types of wax, their internal behaviors and the flight activity of these bees. The experiments were conducted at the Federal Institute of Paraíba, Sousa campus, in October 2023. Four Jandaíra bee colonies were used, kept in boxes, a northeastern model, with a glass inner side, allowing observations inside the boxes. Circular containers containing different types of wax were placed in each box. After 12:00 o’clock the containers containing the least and most preferred waxes were inverted. Bees were counted in each of the containers every thirty minutes. Additionally, the entry and exit of bees were counted (for a period of 10 minutes every 30 minutes). The data were subjected to the Q-square test using the R Core (2003) software. Uruçú beeswax was the most preferred over the others. In the study of flight activity, peaks of bee departures were observed in the late morning and early afternoon. Peaks were observed at 08:20, 11:20 and 15:20. It can be concluded that: Uruçu beeswax was the most preferred among those studied, in the morning and afternoon, followed by Africanized beeswax. During flight activity, peaks in departures and arrivals can be seen, varying depending on the time of day and between boxes.